Synthesis and characterization of activated carbon from palm kernel shells for electrochemical double layer capacitor - Nurul Khairiyyah, Mohd Zain (2015)
Storage of electrical energy at an electrode–electrolyte interface under supercapacitive mode is intriguing owing to its large power capability compared to batteries. A large electrode surface is required for storing large amount of energy and high electrical conductivity of the electrode and electrolyte enable high rate delivery. Furthermore, primary material supply should be ensured for a research result to be adopted by industry. These requirements make carbons, in all of its allotropes, as a desirable candidate as an electrode material for supercapacitors. Biomass provides as an excellent source of carbon considering the renewability; however, properties of biomass even from similar species strongly vary depending on the geographical location. Malaysia is the largest exporter of palm oil; for each 2.5 kg of crude palm oil over 100 kg of biomass is produced as a byproduct. Palm oil produces six main biomass types such as fronds, trunks, empty fruit bunches, palm kernel shells (PKS), mesocarp fiber and palm oil mill effluent. Among them PKS contribute ~6%. However, use of PKS as a source of carbon for supercapacitors electrode has not been tested so far. This research thesis aims to evaluate the electrochemical properties of the carbon produced from PKS. Decomposition behavior of cleaned PKS was studied using thermogravimetric analysis and accordingly carbonized by pyrolysis. The as-prepared char was chemically activated using KOH, NaOH, H2SO4, and ZnCl2 in four impregnation ratios and optimized for the best surface properties. The structure and microstructure of the activated carbon were studied using X- ray diffraction and scanning electron microscopy, respectively. The electrochemical properties of all the sixteen samples obtained under various activation conditions were studied by cyclic voltammetry, galvanostatic charge-discharge cycling and electrochemical impedance spectroscopy in a three-electrode system configuration using electrodes prepared from the PKS activated carbon (AC) as working electrode, Pt wire as counter electrode, and Hg/HgO as reference electrode in 1 M KOH electrolyte. The electrochemical properties were correlated with the surface properties in detail. Finally, a working supercapacitor is fabricated using the PKS AC electrodes developed on nickel foam substrate, glassy fiber as a separator, and 1 M KOH as electrolyte. The device delivered energy densities 6.6, 6.0, 5.7, 5.2, 4.5, 4.1, 3.5, 3.0 Wh/kg at power densities 60, 180, 310, 600, 1200, 1800, 300, 4000 W/kg, respectively. These values are comparable to the commercially available devices using activated carbon. Owing to the large abundance of carbon and promising results herewith, the present results show huge promise in developing PKS ACs as commercial supercapacitor electrodes.